Methodology for Developing Moral and National Values in Students Through Historical Knowledge - Raykhona Surobova Zokirjonovna (Scientific Trends, 2025)
This article presents methodologies for developing moral and national values in youth through historical knowledge. By understanding specific historical events, students see where human life, dignity, rights, and spiritual virtues were neglected. Through these moral lessons, they not only gain insight into the distant past but also learn to reflect on various ethical situations in their own lives. Assessment and Modernization of the Methodology. The main pillar of our new methodology (TFTAX) is the integration of scientific rigor and practical applicability. This methodological process should be regularly evaluated and, if necessary, modernized.
Keywords: History, theory, moral values, pedagogy, youth, globalization, education, historical processes, methodology.